Influence of Soil Properties on Phosphorus Dynamics and Phosphatase Enzyme Activity in Agricultural Soils of Central Nepal - Khadka, Dinesh; Pande, Keshab Raj; Tripathi, Bhaba Prasad; Bajracharya, Roshan Man (Journal of Nepal Agricultural Research Council, 2024)
A soil system consists of physical, chemical, and biological components that interact to regulate nutrient availability, water retention, and ecosystem stability. Soil phosphorus (P) fractions, phosphatase enzyme activity, and P adsorption-desorption characteristics are crucial for sustainable P management and are influenced by various intrinsic and extrinsic factors. However, the characteristics of these parameters in Nepalese soils remain largely unexplored. This study assessed the influence of soil properties on these parameters by analyzing 225 soil samples collected from various locations in central Nepal. Key soil properties, including pH, EC, OM, CaCO3, CEC, exchangeable Al, sand, silt, clay, total N, and available nutrients (P, K, Ca, Mg, S, B, Cu, Mn, Fe, and Zn), were measured, alongside response variables such as P fractions, phosphatase enzyme activity, and P adsorption-desorption characteristics, using standard analytical methods. Statistical analyses, including Pearson’s correlation and redundancy analysis (RDA), were applied. The results showed that soil properties accounted for 58.63%, 53.65%, 56.62%, and 38.37% of the total variation in P fractions, phosphatase enzyme activity, P adsorption, and P desorption characteristics, respectively. Fifteen soil properties significantly influenced P fractions, ranked in decreasing order of impact: OM, Olsen P, pH, CEC, Fe, CaCO3, Cu, clay content, sand content, EC, K, Ca, Zn, Mg, and total N. Twelve properties significantly affected phosphatase enzyme activity, listed in decreasing order as OM, pH, available Ca, CaCO3, B, EC, P, CEC, Zn, K, sand content, and clay content. For P adsorption, twelve properties had significant effects, ranked as follows: Olsen P, sand content, pH, B, CaCO3, Cu, Ca, EC, OM, K, CEC, and clay content. Thirteen properties significantly impacted P desorption, listed in decreasing order as OM, sand content, Olsen P, EC, pH, Cu, Zn, CaCO3, K, B, CEC, Fe, and Ca. These findings highlight the critical role of specific soil properties in regulating P dynamics, providing valuable insights for enhancing P management strategies in diverse agricultural systems.